2019
DOI: 10.2196/12488
|View full text |Cite
|
Sign up to set email alerts
|

Digital Education for the Management of Chronic Wounds in Health Care Professionals: Protocol for a Systematic Review by the Digital Health Education Collaboration

Abstract: Background Digital education is “the act of teaching and learning by means of digital technologies.” Digital education comprises a wide range of interventions that can be broadly divided into offline digital education, online digital education, digital game-based learning, massive open online courses (MOOCs), psychomotor skills trainers, virtual reality environments, virtual patient simulations, and m-learning. Chronic wounds pose an immense economic and psychosocial burden to patients and the hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…Digital education was a broad construct describing a wide range of teaching and learning strategies that were exclusively based on the use of electronic media and devices as training, communication, and interactions tools [ 19 ]. These aspects could pertain to educational approaches, concepts, methods, or technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Digital education was a broad construct describing a wide range of teaching and learning strategies that were exclusively based on the use of electronic media and devices as training, communication, and interactions tools [ 19 ]. These aspects could pertain to educational approaches, concepts, methods, or technologies.…”
Section: Methodsmentioning
confidence: 99%
“…E-learning modalities can include offline or online educational activities. 7 Additionally, this form of learning can range from a basic conversion of in-person content to digital format to a more complex deployment of digital technologies (eg, mobile education, virtual patients, and virtual reality) 6 E-learning can provide more flexible solutions for busy clinicians, allowing them to choose suitable times to work. It can also allow students to be more independent, as it is self-paced.…”
Section: Introductionmentioning
confidence: 99%
“…The MOOC final certificates that might be important in continuous education can be both voluntary (Pérez‐Moreno et al 2018) and compulsory (Harvey et al 2017). Evaluation systems seem to be based mainly on knowledge acquisition and degree of engagement, thus leaving open the question of the effectiveness of this continuous education tool for maintaining practical competencies (Martinengo et al 2019). Evaluation heterogeneity across studies can affect participation and dropout rates that—when reported—have been documented as high (Jia et al 2019; Scott et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple advantages, MOOCs have been documented to have weaknesses such as (a) the high dropout rates, which can be as high as 85% of participants (Wang et al 2019), (b) the challenged evaluation of learning outcomes, especially in terms of acquired technical and practical skills (Martinengo et al 2019), and (c) the risk of falling into a too standardized approach (Skiba 2017). research designs and of merging research methods used by investigators and to find out gaps in the existing evidence (Munn et al 2018), a scoping review was performed.…”
Section: Massive Online Open Coursesmentioning
confidence: 99%